2020
DOI: 10.1002/cl2.1118
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Improving access to health and social services for individuals experiencing, or at risk of experiencing, homelessness

Abstract: The title should be in headline style summarising the main findings of the review, for example, "enforcing conditions makes cash transfers more effective in increasing enrolments" and "detention of asylum seekers has adverse effects on mental health". The title for empty reviews can state that there is no evidence, for example, "there is no rigorous evidence on the effectiveness of refugee resettlement programs". Titles can also reflect the size of the effects or the quality of the evidence, for example, "Limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, the map also showed that homelessness is an 'under-reviewed' area: of the 264 studies in the first map, only 21 -fewer than 10% -were reviews, and most these reviews were in the health sector. The map was used to identify three priority topic areas for which reviews were commissioned from Queen's University Belfast: discharge, access to health, and accommodation-based approaches (Hanratty et al, 2020;Miller et al, 2020;and Keenan et al, 2020, respectively). The reviews were based on the studies in the map so no additional search was required.…”
Section: Case Studies Nos 3 and 4: The Uk What Work Centres -Chi And Yefmentioning
confidence: 99%
“…However, the map also showed that homelessness is an 'under-reviewed' area: of the 264 studies in the first map, only 21 -fewer than 10% -were reviews, and most these reviews were in the health sector. The map was used to identify three priority topic areas for which reviews were commissioned from Queen's University Belfast: discharge, access to health, and accommodation-based approaches (Hanratty et al, 2020;Miller et al, 2020;and Keenan et al, 2020, respectively). The reviews were based on the studies in the map so no additional search was required.…”
Section: Case Studies Nos 3 and 4: The Uk What Work Centres -Chi And Yefmentioning
confidence: 99%